Consumer Feedback following Participation in a Family-Based Intervention for Youth Mental Health. (5th September 2012) - Lewis, Andrew J.; Bertino, Melanie D.; Robertson, Narelle; Knight, Tess; Toumbourou, John W.
Abstract : Background . This paper presents findings derived from consumer feedback, following a multicentre randomised controlled trial for adolescent mental health problems and substance misuse. The paper focuses on the implementation of a family-based intervention, including fidelity of delivery, family members' experiences, and their suggestions for program improvements. Methods . Qualitative and quantitative data (n = 21 ) were drawn from the Deakin Family Options trial consumer focus groups, which occurred six months after the completion of the trial. Consumer focus groups were held in both metropolitan and regional locations in Victoria, Australia. Findings . Overall reductions in parental isolation, increases in parental self-care, and increased separation/individuation were the key therapeutic features of the intervention. Sharing family experiences with other parents was a key supportive factor, which improved parenting confidence and efficacy and potentially reduced family conflict. Consumer feedback also led to further development of the intervention, with a greater focus on aiding parents to engage adolescents in services and addressing family factors related to adolescent's mood and anxiety symptoms. Conclusions . Participant feedback provides valuable qualitative data, to monitor the fidelity of treatment implementation within a trial, to confirm predictions about the effective mechanisms of an intervention, and to inform the development of new interventions.